The effects of Jazz artists’ collaboration works: a study of Larry Carlton - Mohamed Razali, Camellia Siti Maya; Young, Jin Jae; Salleh, Marzelan (Human Resources Management Academic Research Society (HRMARS), 2024)
Abstract: Jazz musicians have historically released numerous collaboration albums. By focusing on these albums, we may be able to capture a glimpse into the musician’s tendencies before and after producing a collaboration album. During the process of producing and recording a collaboration album, musicians often discover their personal musical strengths and weaknesses, greatly influencing the musician’s tendencies on music. Fusion Jazz is a combination of elements of two music genres, Jazz and Rock music. With musical elements of Jazz and Rock as a foundation, coupled with the incorporation of minor elements from other popular genres, the numerous iterations over the course of time have made this a beloved sub-genre among jazz practitioners. This becomes apparent as more jazz musicians begin to include Fusion Jazz compositions in their repertoire shortly after collaborating with Fusion Jazz musicians. Thus, this study is to ascertain the musical identity resulting from collaboration work among musicians by conducting a meticulous analysis of Larry Carlton's music both prior to and subsequent to such collaborations. Through this research, we aim to discern and elucidate the distinctive characteristics and stylistic influences that emerge in Carlton's music as a direct result of his collaborative endeavors with other artists. Consequently, this study will endeavor to prognosticate potential future trends in Fusion Jazz.